Restorative Retelling for Processing Psychedelic Experiences: Rationale and Case Study of Complicated Grief - González, Débora; Aixalà, Marc B.; Neimeyer, Robert A.; Cantillo, Jordi; Nicolson, Donald; Farré, Magi (Frontiers in Psychology, 2022)
Rationale Many psychedelic experiences are meaningful, but ineffable. Engaging in meaning-making regarding emerging symbolic content and changing previous schemas have been proposed as mechanisms of change in psychedelic therapy. Objective Firstly, we suggest the implementation of a Restorative Retelling (RR) technique to process and integrate the psychedelic experience into autobiographical memory, in a way that fosters meaning-making. We also show how ayahuasca has the potential to evoke key psychological content in survivors, during the process of grief adjustment following the death of a loved one. Methods The rationale for the implementation of RR to process psychedelic experiences and a case study of a woman suffering from Complicated Grief (CG) after her mother’s suicide are presented. Results Evaluations conducted before the ayahuasca experience and after RR suggest the effectiveness of ayahuasca and RR in reducing symptoms of CG and psychopathology. Conclusion This case report illustrates an effective adaptation of the RR technique for processing the psychedelic experience. The significance of the study and its limitations are discussed.